Corrosion‐Resistant Hybrid Nanoparticles of Polydimethylsiloxane@Fe Obtained by Thermolysis of Fe(CO)5. Issue 10 (9th March 2016) - Aouat, Yohann; Marom, Gad; Avnir, David
Abstract: Thermal decomposition of iron pentacarbonyl, Fe(CO)5, in the presence of small amounts of polydimethylsiloxanes (PDMSs) leads to a hybrid aggregate of pure nanosized (about 10 nm) zero‐valent iron nanoparticles (PDMS@Fe) with remarkable corrosion‐resistance properties even after three months of immersion in saline solution. Various tests, including potentiodynamic polarization measurements and impedance spectroscopy, were carried out in a 3.5 wt.‐% NaCl solution; the results indicate a corrosion protection efficiency ( η, %) of up to 99.7 % and an iron corrosion rate estimation of 3 µm per year. Detailed characterization of the materials, including Mössbauer spectroscopy and magnetization measurements, was used to provide a mechanism for the remarkable corrosion inhibition properties of this PDMS‐doped iron nanohybrid. Abstract : Thermal decomposition of Fe(CO)5 in the presence of small amounts of polydimethylsiloxanes (PDMSs) leads to a hybrid aggregate of pure nanosized (about 10 nm) zero‐valent iron nanoparticles (PDMS@Fe) with remarkable corrosion‐resistance properties with a corrosion rate lower than 3 µm per year.